2019
DOI: 10.1155/2019/7547382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetyl Cysteine on Intracerebroventricular Colchicine Induced Cognitive Deficits, Beta Amyloid Pathology, and Glial Cells

Abstract: Among the many factors responsible for the cognitive decline in Alzheimer’s disease, beta amyloid protein and plaque formation is crucial. This amyloid pathology is associated with activation of glial cells and oxidative stress but whether oxidative stress activates beta amyloid protein in the neurons is not clear. Further the expression of microglia is also known to vary during pathogenesis of beta amyloid plaques. The aim of the present study is to evaluate the antioxidant effect of NAC on amyloid pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…*P < 0.05 versus normal control, #P < 0.05 versus untreated AD rats, €P < 0.05 versus sacubitril/ valsartan-treated rats inducing oxidative stress, microtubule disruption, cholinergic system dysfunction, and increasing the expression of beta amyloid protein. This results in abnormal accumulation of Aβ peptide in brain [21]. In accordance with previous studies [18,21,39], icv injection of colchicine in the untreated AD group increased escape RLs across learning days and decreased time spent in target quadrant in MWM test.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…*P < 0.05 versus normal control, #P < 0.05 versus untreated AD rats, €P < 0.05 versus sacubitril/ valsartan-treated rats inducing oxidative stress, microtubule disruption, cholinergic system dysfunction, and increasing the expression of beta amyloid protein. This results in abnormal accumulation of Aβ peptide in brain [21]. In accordance with previous studies [18,21,39], icv injection of colchicine in the untreated AD group increased escape RLs across learning days and decreased time spent in target quadrant in MWM test.…”
Section: Discussionsupporting
confidence: 90%
“…This results in abnormal accumulation of Aβ peptide in brain [21]. In accordance with previous studies [18,21,39], icv injection of colchicine in the untreated AD group increased escape RLs across learning days and decreased time spent in target quadrant in MWM test. In addition, it lowered RL in passive avoidance task.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Animal studies have shown significant promise improving cognitive function even though beta-amyloid pathology was unchanged [ 113 ]. There is some evidence that NAC as an adjuvant may slow the progression of dementia; however, this effect was seen clinically in a nutraceutical containing several ingredients including NAC [ 114 ].…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…5 ) and astrocytes (Fig. 6 ) were done according to the protocol of Streit ( 1990 ) and Joy et al ( 2019 ). The quantitative analysis was done under light microscopy (20X).…”
Section: Methodsmentioning
confidence: 99%